MAKNA PEMBELAJARAN DARING BAGI MAHASISWA KEPERAWATAN - Muhammad Alfin; Wasisto Utomo; Erika Erika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
The current state of the COVID-19 pandemic has changed the face-to-face learning process, changing all activities to being fully online. Online learning is a new learning method used by students and educators in the teaching and learning process. Nursing students face various challenges related to the implementation of online learning policies. This research is qualitative research using a phenomenological approach. This study aims to find out more about the experiences of nursing students regarding online learning in the COVID-19 pandemic situation in 2021. The sample in this study was taken using the Purposive Sampling method. With the data collection process, namely semi-structured interviews using interview guidelines that have been prepared according to research objectives. Participants consisted of 1 male and 6 female. The results of this study obtained thema namely the meaning of online learningIt can be concluded that the nursing student experience regarding online learning is how students interpret online learning.Keywords: COVID-19;online learning; phenomenological study